THE EFFECT OF LIQUIDITY AND PROFITABILITY TO THE VALUE OF BANKING COMPANIES REGISTERED IN INDONESIA STOCK EXCHANGE - Zulfika, Zairi; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to test partially and simultaneously the influence of liquidity and profitability on the value of banking companies. Where independent variable in this research is liquidity and profitability while dependent variable is company value. Sources of data used are secondary data derived from the financial statements of Banking companies listed on the Indonesia Stock Exchange (IDX) period 2010-2015. Samples were taken by purposive sampling and samples that met the selection criteria. The sample used is 5 companies. Multiple regression is used to analyze the data in this research. Partial research results indicate that the liquidity (banking ratio) does not affect the value of corporate (PBV) banking in the sample company. This is evidenced by the value of t arithmetic equal to -1,612 and p value 0,118. While the research shows that profitability (ROA) affects the value of corporate (PBV) banking in the sample company. Evidenced by the value of t arithmetic of 0,081 and p value 0,936. The result of simultaneous research get simultaneous result of liquidity (banking ratio) and profitability (ROA) influence to company value (PBV) of banking at sample company, This is proved by F value count 5,284 and p value 0,001. Keywords: Profitability (Banking Ratio), Liquidity (ROA) and Corporate Value (PBV).